2009
DOI: 10.1007/s00267-009-9370-0
|View full text |Cite
|
Sign up to set email alerts
|

Water Consumption in the Production of Ethanol and Petroleum Gasoline

Abstract: We assessed current water consumption during liquid fuel production, evaluating major steps of fuel lifecycle for five fuel pathways: bioethanol from corn, bioethanol from cellulosic feedstocks, gasoline from U.S. conventional crude obtained from onshore wells, gasoline from Saudi Arabian crude, and gasoline from Canadian oil sands. Our analysis revealed that the amount of irrigation water used to grow biofuel feedstocks varies significantly from one region to another and that water consumption for biofuel pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 16 publications
4
105
0
1
Order By: Relevance
“…6), similar to that of conventional oil sands production. 35 Switchgrass-derived ethanol (Case 3) requires less blue water than corn stover-derived ethanol (Case 1 or 2) because of savings from switchgrass irrigation. Export bioelectricity contributes a 1 gal/gal water credit to the blue water footprint, reducing total blue water use by 12-20%.…”
Section: Resultsmentioning
confidence: 99%
“…6), similar to that of conventional oil sands production. 35 Switchgrass-derived ethanol (Case 3) requires less blue water than corn stover-derived ethanol (Case 1 or 2) because of savings from switchgrass irrigation. Export bioelectricity contributes a 1 gal/gal water credit to the blue water footprint, reducing total blue water use by 12-20%.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, most fuel ethanol is purified by distillation, which requires large amounts of water and energy (40). Water used for cooling distillation towers usually accounts for over 50% of total water consumption, and the energy needed for heating distillation columns consumes about 75% of total process heat (18,20,41). However, potential savings would need to be weighed against the cost of chemical conversion of acetaldehyde and H 2 to ethanol.…”
mentioning
confidence: 99%
“…The average value (weighted by 2007 ethanol production) was 142 L/L, although as the authors pointed out, national average values are not relevant in understanding bioethanol's water implications at a local scale. Also in 2009, Wu et al published a life-cycle report confirming that crop irrigation is the most important factor determining total water consumption in providing corn ethanol in the USA and demonstrating the large regional variability of irrigation requirements [21]. Results showed that 70% of the corn used to produce ethanol in 2009 was grown in regions that required 10-17 L/L; whereas 19% of the corn was grown in regions that required over 300 L/L.…”
Section: Current Water Requirements For Corn Ethanolmentioning
confidence: 97%
“…Results taken from five recent life-cycle assessment (LCA) studies are summarized graphically in Fig. 2 [21,[26][27][28][29]. As shown here, the consumptive water use of corn ethanol in the USA is 1-2 orders of magnitude higher than that of petroleumbased fuels.…”
Section: Current Water Requirements For Corn Ethanolmentioning
confidence: 99%